2011
DOI: 10.1161/hypertensionaha.110.167957
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Form of the (Pro)Renin Receptor Is Augmented in the Collecting Duct and Urine of Chronic Angiotensin II–Dependent Hypertensive Rats

Abstract: Renin synthesis and secretion by principal cells of the collecting duct (CD) is enhanced in angiotensin (Ang) II-dependent hypertension. The presence of renin/(pro)renin and its receptor, the (pro)renin receptor [(P)RR], in the CD may provide a pathway for Ang I generation with further conversion to Ang II. To assess if (P)RR activation occurs during Ang II-dependent hypertension, we examined renal (P)RR levels and soluble (P)RR (s(P)RR) excretion in the urine of chronic Ang II-infused rats (80 ng/min; for 2-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
163
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 134 publications
(172 citation statements)
references
References 32 publications
8
163
1
Order By: Relevance
“…Indeed, the demonstrations that ANG II and AVP can directly stimulate epithelial sodium channels in the CD (10, 33) and suggest a parallel pathway for the stimulation of synthesis and secretion of prorenin-renin, as well as of AQP-2 expression, in the principal cells. Furthermore, the binding of renin and prorenin to the (pro)renin receptor on the apical side of the CD may help prevent the losses of these proteins in the urine (11) and may also contribute to increase their catalytic activity to further increase intratubular ANG II generation (11,13). Importantly, it has been shown that plasma AVP concentrations are increased in some patients with heart failure, despite hyponatremia and low plasma osmolality (45).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the demonstrations that ANG II and AVP can directly stimulate epithelial sodium channels in the CD (10, 33) and suggest a parallel pathway for the stimulation of synthesis and secretion of prorenin-renin, as well as of AQP-2 expression, in the principal cells. Furthermore, the binding of renin and prorenin to the (pro)renin receptor on the apical side of the CD may help prevent the losses of these proteins in the urine (11) and may also contribute to increase their catalytic activity to further increase intratubular ANG II generation (11,13). Importantly, it has been shown that plasma AVP concentrations are increased in some patients with heart failure, despite hyponatremia and low plasma osmolality (45).…”
Section: Discussionmentioning
confidence: 99%
“…Renin content in cell culture media was determined by using modified protocols from the PRA assay [GammaCoat Plasma Renin Activity 125I RIA kit (DiaSorin, Stillwater, MN)] as previously described (8).…”
Section: Methodsmentioning
confidence: 99%
“…(P)RR undergoes proteolytic cleavage to generate soluble (P)RR (128,129). (P)RR is easily detected in type A intercalated cells and not in principal cells (130,131). Binding of renin and prorenin to (P)RR increases the catalytic efficiency of these enzymes in the conversion of angiotensinogen to angiotensin by 4-fold.…”
Section: Regulation Of Intercalated Cell Transport Proteins Bymentioning
confidence: 99%